Genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) from Malaysia, with description of three new species - Liu, Chen; Wang, Shuxia (Zootaxa, 2020)
Based on the specimens collected in Mt. Trusmadi, Sabah, Malaysia, three new species of the genus Promalactis are described: P. clavivalvata sp. nov., P. abasiloba sp. nov. and P. trusmadiensis sp. nov. In addition, females of three previously known species (P. folivalva Wang, 2018, P. sectoralis Wang et al., 2013 and P. trigonilobata Wang, 2018) are described for the first time. Two species (P. sectoralis Wang et al., 2013 and P. pileata Wang, 2019) are newly recorded for Malaysia. Images of both adults and genitalia of the new species and the genitalia of the newly described females are provided.